Records management in aid of social transformation in Nigeria (2007)
Records constitute a vital tool for decision-making. Availability of the right information to the right person at the right time guarantees a well-informed decision which can impact positively on society. Besides, records constitute the enduring memory of a nation, as they document the activities of its people and institutions. The knowledge of such activities is crucial to planning and development. Unless records are properly managed, access will be difficult if not impossible. This paper, therefore, discusses the basic process of records management and highlights its benefits in ensuring access to valuable information that is required for social transformation.